Dendrobionts bedbags (Heteroptera, Pentatomidae) of the especially protected natural territories of the South-East Kazakhstan (Experimental biology, 2018)
In protected areas in South-East Kazakhstan: State national natural parks (SNNP) "Kоlsay kоlderі", "Altyn-Emel", "Sharyn", "Ile-Alatau" and "Alakol" Reserve conducted an inventory and a comprehensive analysis of the fauna dendrobionts and compiled an annotated list including 23 species, of which 2 species included in the Red book of Almaty region: Arma custos (Fabricius, 1794) and Zicrona caerulea (Linnaeus, 1758). Eating animal foods tend to 8 species, other species feed on plant foods, of which 10 species – polyphytophages, 2 - wide oligophytophages, 3 - narrow oligophytophages. For dendrobionts of the specially protected natural areas in South-East Kazakhstan is characterized by 1 type of the voltinizm: monovoltinizm. Different types of Hemiptera have different requirements for the degree of hydration of habitat. On this basis we identified the following types of environmental groups: mesophyles - 78.3%, xeromezofyles - 8.7%, mezoxerofyles - 4.3%, xerophyles - 8.7%. Among wintering in the adult stage - 20 species overwinters in the larval stage only 1 type - is Pentatoma rufipes (Linneaus, 1758), and in the stage of eggs overwinter 2 types (Picromerus bidens (Linnaeus, 1758), P. lewisi (Scott, 1874). Types usually appear first wintering on the adult stage, the majority of such species - 87%, in the stage of eggs - 8.7%, in the larval stage - 4.3%.